2021
DOI: 10.1177/0734016821996795
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Differential Impact of Vacancy on Criminal Violence in the City of St. Louis, MO

Abstract: This study employs risk terrain modeling to identify the spatial correlates of aggravated assault and homicide in St. Louis, MO. We build upon the empirical literature by (1) replicating recent research examining the role of vacancy in the concentration of criminal violence and (2) examining whether the environmental correlates of violence vary between north and south St. Louis, a boundary that has long divided the city along racial and socioeconomic lines. Our results indicate that vacancy presents a strong, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Underscoring these differences, those from high tax delinquency neighborhoods are also more likely to die at an earlier age (Zuberi & Teixeira, 2021). Similarly, a recent study found that the number of tax delinquent and vacant properties in a neighborhood also predict greater rates of violent crime (Fox et al, 2021). Despite this evidence, no known research has examined the potential for divergent sources of neighborhood instability to differentially predict violence at the neighborhood level.…”
Section: Neighborhood Residential Stability and Violencementioning
confidence: 99%
“…Underscoring these differences, those from high tax delinquency neighborhoods are also more likely to die at an earlier age (Zuberi & Teixeira, 2021). Similarly, a recent study found that the number of tax delinquent and vacant properties in a neighborhood also predict greater rates of violent crime (Fox et al, 2021). Despite this evidence, no known research has examined the potential for divergent sources of neighborhood instability to differentially predict violence at the neighborhood level.…”
Section: Neighborhood Residential Stability and Violencementioning
confidence: 99%
“…Fourth, the set of urban features that we included in the spatiotemporal analysis can be extended to include additional features. For example, Fox et al [75] found vacancy as the key driver of violent crime across the north and south sides of St. Louis, MO. Lastly, the sample is limited to Chicago, IL, which significantly curbs the generalizability of this study to other cities.…”
Section: Limitationsmentioning
confidence: 99%
“…Underscoring these differences, those from high tax delinquency neighborhoods are also more likely to die at an earlier age [ 22 ]. Similarly, a recent study found that the number of tax delinquent and vacant properties in a neighborhood also predict greater rates of violent crime [ 23 ]. Despite this evidence, no known research has examined the potential for divergent sources of neighborhood instability to differentially predict violence at the neighborhood level.…”
Section: Introductionmentioning
confidence: 99%